FINITE ELEMENT ANALYSIS OF CARBIDE TOOL MACHINING LOADS AND RESPONSES ON HIGH STRENGTH MATERIALS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The cutting tool material is a function of the chemical, mechanical and thermal properties ofthe cutting tool material to the work-piece. With the trend towards miniaturization, micromachininghas become more and more critical in fabricating micro parts. The micromachiningprocess involved in this study is micro-milling the conventional micro endmilling, 4-flutes micro end milling. Cemented carbide is the material that has been used forthis study. The main problem with the flutes micro end milling is it quickly wears in a shorttime. In this study, Static structural analysis of the different work-piece materials the toolswill be modeller and simulated using Ansys Working with other materials such as coatedInconel 625, SS316 tools Workbench 2020R1 is well-designed software.